Household air pollution from solid fuel use as a dose-dependent risk factor for cognitive impairment in northern China - Tseng, Tzu-Wei Joy; Carter, Ellison; Yan, Li; Chan, Queenie; Elliott, Paul; Ezzati, Majid; Kelly, Frank; Schauer, James J.; Wu, Yangfeng; Yang, Xudong; Zhao, Liancheng; Baumgartner, Jill (Scientific reports, 2022)
The relationship between exposure to household air pollution (HAP) from solid fuel use and cognition remains poorly understood. Among 401 older adults in peri-urban northern China enrolled in the INTERMAP-China Prospective Study, we estimated the associations between exposure to HAP and z-standardized domain-specific and overall cognitive scores from the Montreal Cognitive Assessment. Interquartile range increases in exposures to fine particulate matter (53.2-µg/m 3 ) and black carbon (0.9-µg/m 3 ) were linearly associated with lower overall cognition [− 0.13 (95% confidence interval: − 0.22, − 0.04) and − 0.10 (− 0.19, − 0.01), respectively]. Using solid fuel indoors and greater intensity of its use were also associated with lower overall cognition (range of point estimates: − 0.13 to − 0.03), though confidence intervals included zero. Among individual cognitive domains, attention had the largest associations with most exposure measures. Our findings indicate that exposure to HAP may be a dose-dependent risk factor for cognitive impairment. As exposure to HAP remains pervasive in China and worldwide, reducing exposure through the promotion of less-polluting stoves and fuels may be a population-wide intervention strategy to lessen the burden of cognitive impairment.